Anti-aging light-cured polyurethane acrylate blending composition, OCA adhesive film and preparation method of OCA adhesive film
By using cashew shell oil diol and diisocyanate in the photocured polyacrylate glue, combined with active diluents and acrylate compounds, a photocured polyurethane acrylate blend composition is prepared, which solves the problem of difficult to take into account both the light transmittance and aging resistance of films in the field of optical display, and achieves a film with high light transmittance and high aging resistance.
Patent Information
- Application Number
- CN202411957792.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-05-02
AI Technical Summary
It is difficult to take into account high light transmittance and good aging resistance in the application of existing photocuring polyacrylate glues in the field of optical display.
Aging-resistant photocuring polyurethane acrylate blend composition is prepared by controlling the content of the soft and hard segments and the amount of active diluents.
The mechanical properties and aging resistance of the photocured polyurethane acrylate blend composition are significantly improved, ensuring high light transmittance (>90%) and high 180° peel strength, suitable for optical display fields.
Smart Images

Figure BDA0005216647080000101
Abstract
Description
Technical Field
[0001] The present application relates to an anti-aging photocurable polyurethane acrylate blend composition, an OCA adhesive film and a preparation method thereof, and belongs to the technical field of adhesive compositions. Background Art
[0002] Light-curing acrylic adhesive has received extensive attention and development due to its environmental protection, easy coating, simple process and other advantages. Light-curing polyacrylate adhesive mainly uses light-curing resin, reactive diluent, additive and photoinitiator as raw materials, and is cured under ultraviolet light. Polyacrylate adhesives usually have excellent adhesion and can bond a variety of substrates such as plastics and metals. They are widely used in aerospace, consumer electronics, transportation and other fields.
[0003] Ordinary light-curing polyacrylate adhesive has a low cross-linking density, and its main chain contains hydrophilic carboxyl, hydroxyl and easily hydrolyzed ester bonds, so its aging resistance is poor. If you want to prepare a light-curing polyacrylate adhesive with good bonding strength and aging resistance, it is difficult to obtain good results by simply using one type of resin, and it must be modified. For example, using silicone monomers, resins or rubber to modify light-curing acrylic adhesives, and modifying polyacrylates by physical blending or chemical copolymerization can not only maintain the inherent advantages of polyacrylate adhesives, but also improve their temperature resistance, water resistance and medium resistance.
[0004] Polyacrylate adhesive is widely used in the field of optical display. For such applications, polyacrylate adhesive is required to have high light transmittance, good aging resistance, stable peeling force and other properties to meet its bonding effect in harsh ambient temperature. The patent with publication number CN105505302A discloses a light-cured polyacrylate adhesive, which is modified by an acrylate monomer with an epoxy-terminated polysiloxane, and then reacted with an isocyanate-containing siloxane monomer to obtain a double bond and methylsiloxy / ethylsiloxy resin in two steps. This method is complex in process and has poor stability, and the main resin is a polysiloxane structure with low cohesion. The patent with publication number JP2005136298A discloses a polyacrylate adhesive containing an isocyanate and epoxy group crosslinking agent, but the film stability is poor, and residual adhesive is easily produced when peeled off. Therefore, there is an urgent need for a polyurethane acrylate blend composition that is resistant to aging and has high light transmittance to meet the application requirements in the field of optical display. Summary of the invention
[0005] The problem that it is difficult to achieve both high light transmittance and good aging resistance in the application of polyacrylate adhesive in the field of optical display has not been solved. The present application provides a technical solution for an aging-resistant photocurable polyurethane acrylate blended composition. In the synthesis, two cashew nut shell oil diols with different hydroxyl values are used as the soft segment of the resin, diisocyanate is introduced as the hard segment of the resin, and an acrylic ester compound containing active hydroxyl groups is used as a capping agent. The composition containing the polyurethane acrylate resin has good compatibility, high light transmittance (greater than 90%), high 180° peel strength under high temperature aging and room temperature, and can be used as an optical display material in the field of optical display.
[0006] This application adopts the following technical solutions:
[0007] According to the first aspect of the present application, there is provided an aging-resistant photocurable polyurethane acrylate blend composition, the aging-resistant photocurable polyurethane acrylate blend composition comprising:
[0008] Reactive diluent, double-bond terminated polyurethane acrylate resin;
[0009] The double-bond terminated polyurethane acrylate resin comprises a soft segment, a hard segment and a capping agent;
[0010] The soft segment is selected from cashew nut shell oil diol;
[0011] The hard segment is selected from diisocyanates;
[0012] The end-capping agent is selected from acrylic acid ester compounds containing active hydroxyl groups.
[0013] Optionally, the cashew nut shell oil diol has a hydroxyl value of 55 to 100 mgKOH / g.
[0014] Optionally, the number average molecular weight of the double-bond terminated polyurethane acrylate resin is 3,000 to 10,000.
[0015] Optionally, the number average molecular weight of the double-bond terminated polyurethane acrylate resin is 4000-8000.
[0016] Optionally, the double-bond terminated polyurethane acrylate resin has a viscosity of 5000 to 15000 cps at 25°C.
[0017] Optionally, the double-bond terminated polyurethane acrylate resin has a viscosity of 6000 to 14000 cps at 25°C.
[0018] Optionally, in the double-bond terminated polyurethane acrylate resin, the content of the soft segment is 60 to 90 wt %, the content of the hard segment is 10 to 30 wt %, and the content of the end-capping agent is 1 to 6 wt %.
[0019] Optionally, in the double-bond terminated polyurethane acrylate resin, the total content of the soft segment, the hard segment and the end-capping agent is 100%.
[0020] Optionally, the diisocyanate is selected from at least one of isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and 1,4-cyclohexanedimethyl diisocyanate.
[0021] Optionally, the acrylic acid ester compound containing active hydroxyl groups is selected from at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate and hydroxypropyl methacrylate.
[0022] The present application can significantly improve the mechanical properties of the photocurable polyurethane acrylate blended composition by controlling the content of the soft and hard segments in the polyurethane acrylate resin to meet the above-mentioned restrictions, and improve its 180° peel strength at room temperature and high temperature and high humidity. The mechanism of action is inferred to be the presence of the polar ester bond of the soft segment and the polar urethane bond of the hard segment, which enhances the interaction force of the polar groups on the molecular chain and increases the rigidity of the molecular chain. In addition, the long carbon chain on the side chain of the cashew nut shell oil diol in the soft segment improves the hydrophobicity. Therefore, the 180° peel strength of the photocurable polyurethane acrylate blended composition is improved under high temperature and high humidity aging conditions.
[0023] Optionally, the reactive diluent is selected from at least one of cyclotrimethylolpropane formal acrylate, trimethylolpropane triacrylate, ethoxyethoxyethyl acrylate, acryloylmorpholine, pentaerythritol triacrylate, N-vinyl pyrrolidone, tripropylene glycol diacrylate, N-vinyl caprolactam, and triethylene glycol diacrylate.
[0024] Optionally, in the aging-resistant photocurable polyurethane acrylate blend composition, the content of the reactive diluent is 10 to 25 wt %.
[0025] Optionally, in the aging-resistant photocurable polyurethane acrylate blend composition, the content of the reactive diluent is 13 to 23 wt %.
[0026] Optionally, the aging-resistant photocurable polyurethane acrylate blend composition also includes a catalyst, and the catalyst is selected from at least one of dibutyltin dilaurate, copper naphthenate, copper isooctanoate, iron naphthenate, iron isooctanoate, zinc naphthenate, zinc isooctanoate, lead naphthenate, lead isooctanoate, dibutyltin isooctyl thioglycolate, and dioctyltin diacetate.
[0027] By controlling the amount of active diluent in the polyurethane acrylate resin blend composition to meet the range defined in the present application, the present invention not only avoids the use of organic solvents, but also significantly reduces the system viscosity during the preparation process of the aging-resistant light-curable polyurethane acrylate blend composition, which is beneficial to the subsequent coating construction. In addition, the cost and difficulty of the resin preparation process are also reduced.
[0028] In the present application, in the synthesis of the double-bond terminated polyurethane acrylate resin, cashew nut shell oil diol with a hydroxyl value of 55 to 100 mgKOH / g is used as the soft segment of the resin, diisocyanate is introduced as the hard segment of the resin, and an acrylate compound containing active hydroxyl groups is used as a capping agent. The composition containing the polyurethane acrylate resin not only has good compatibility and a light transmittance of >90%, but also has high 180° peel strength under high temperature and high humidity, and can be used as an optical display material in the field of optical display.
[0029] According to the second aspect of the present application, a method for preparing the above-mentioned aging-resistant photocurable polyurethane acrylate blend composition is provided, comprising the following steps:
[0030] S1, placing a mixture containing cashew nut shell oil diol, diisocyanate, and active diluent in a reactor, and performing a prepolymerization reaction under an inactive atmosphere to obtain a prepolymer;
[0031] S2. placing a mixture containing the prepolymer, the end-capping agent and the catalyst in a reactor, and performing an end-capping reaction under an inert atmosphere to generate a double-bond end-capped polyurethane acrylate resin, thereby obtaining the anti-aging photocurable polyurethane acrylate blend composition.
[0032] The reactors in step S1 and step S2 are both closed containers, and the reactions are carried out under a standard atmospheric pressure.
[0033] Optionally, in step S1, the conditions of the prepolymerization reaction include: a reaction temperature of 60 to 80° C. and a reaction time of 1 to 4 hours.
[0034] Optionally, in step S1, in the conditions of the prepolymerization reaction, the reaction temperature is selected from any value of 60°C, 65°C, 70°C, 75°C, 80°C or any range therebetween.
[0035] Optionally, in step S1, the reaction time in the prepolymerization reaction conditions is selected from any value of 1 h, 2 h, 3 h, 4 h, or any range between the two.
[0036] Optionally, in step S1, the cashew nut shell oil diol is cashew nut shell oil diol that has been treated with dehydration;
[0037] The dehydration treatment step comprises: placing the cashew nut shell oil diol that has not been dehydrated in a reactor, and dehydrating it at 90-120° C. for 1-4 hours under a vacuum environment.
[0038] The dehydration process is to remove water by reducing the pressure, and the pressure is lower than -0.1MPa.
[0039] The temperature for dehydration in the dehydration step is selected from any value among 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C or any range therebetween.
[0040] The time for dehydration in the dehydration step is selected from any value among 1h, 2h, 3h, 4h or any range between the two.
[0041] In the preparation method of the present application, after the cashew nut shell oil diol is treated to remove water, cross-linking caused by the reaction of water and isocyanate during the prepolymerization reaction is avoided, thereby preventing gelation during the synthesis process.
[0042] Optionally, in step S2, the conditions of the end-capping reaction include: reaction temperature of 60-80° C., and reaction time of 2-5 h.
[0043] Optionally, in step S3, in the conditions of the end-capping reaction, the reaction temperature is selected from any value of 60°C, 65°C, 70°C, 75°C, 80°C or any range therebetween.
[0044] Optionally, in step S3, the reaction time in the capping reaction conditions is selected from any value among 2h, 3h, 4h, 5h or any range between them.
[0045] Optionally, in step S2, the catalyst is selected from at least one of dibutyltin dilaurate, copper naphthenate, copper isooctanoate, iron naphthenate, iron isooctanoate, zinc naphthenate, zinc isooctanoate, lead naphthenate, lead isooctanoate, dibutyltin isooctyl thioglycolate, and dioctyltin diacetate.
[0046] Optionally, the catalyst is used in an amount of 0.01 to 0.5% of the weight of the prepolymer.
[0047] Optionally, the amount of the end-capping agent is 2-5% of the weight of the prepolymer.
[0048] According to a third aspect of the present application, an OCA adhesive film is provided. The OCA adhesive film is obtained by UV curing the above-mentioned aging-resistant photocurable polyurethane acrylate blend composition.
[0049] Optionally, the curing conditions include: irradiating with a high-pressure mercury lamp with a wavelength of 200-400 nm for 5-10 minutes.
[0050] Optionally, the OCA film has a visible light transmittance of >90%, a 180° peeling force of >6N / 25mm at room temperature 25°C, and a 180° peeling force of >6N / 25mm after aging for 500h at high temperature and high humidity (85°C / 85% rh).
[0051] The OCA film described in the present application can be prepared according to conventional curing methods in the art.
[0052] Optionally, the curing step of the OCA film includes:
[0053] After 1-3 parts by weight of the photoinitiator and 100 parts by weight of the anti-aging photocurable polyurethane acrylate blend composition are uniformly mixed, the mixture is poured onto a homemade coating machine covered with a PET release film, the distance between the scraper and the bottom plate is adjusted, the PET release film is pulled, and a film of uniform thickness is formed on the PET film by the scraper, and then light curing is performed to obtain the OCA film.
[0054] The beneficial effects of this application include:
[0055] The anti-aging light-curable polyurethane acrylate blend composition provided by the present application uses two cashew nut shell oil diols with different hydroxyl values as the soft segment of the resin in the synthesis, introduces diisocyanate as the hard segment of the resin, and uses an acrylate compound containing active hydroxyl groups as a capping agent. The composition containing the polyurethane acrylate resin not only has good compatibility, light transmittance>90%, and high 180° peel strength at room temperature and after aging, and can be used as an optical display material in the field of optical display; and, the present application also improves the mechanical properties of the anti-aging light-curable polyurethane acrylate blend composition by controlling the hard segment content of the polyurethane acrylate resin to 10-30wt%, and improves its 180° peel strength at room temperature and after aging. In addition, the preparation method of the anti-aging light-curable polyurethane acrylate blend composition provided by the present application, by adding an active diluent, not only avoids the use of organic solvents, but also can significantly reduce the system viscosity of the anti-aging light-curable polyurethane acrylate blend composition preparation process, and is beneficial to the later coating construction, and also reduces the cost and difficulty of the resin preparation process. DETAILED DESCRIPTION
[0056] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0057] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0058] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0059] The number average molecular weight of the polyurethane acrylate resin was measured by Agilent 1260 gel permeation chromatograph.
[0060] The viscosity of the polyurethane acrylate resin composition is measured using a Brookfield rotational viscometer.
[0061] The contents of the soft segment, hard segment and end-capping agent are calculated based on the feed amount and the remainder of the raw materials. The specific calculation formulas are shown in Formula I, Formula II and Formula III respectively:
[0062] Hard segment content, wt% = W (diisocyanate) / [W (diisocyanate) + W (cashew nut shell oil diol) + W (capping agent)] × 100% Formula I;
[0063] The content of the soft segment, wt% = W (cashew nut shell oil diol) / [W (diisocyanate) + W (cashew nut shell oil diol) + W (capping agent)] × 100% Formula II;
[0064] The content of the end-capping agent, wt% = 100wt% - the content of the hard segment - the content of the soft segment.
[0065] Wherein, in Formula I and Formula II, W (diisocyanate) is the mass of diisocyanate; W (cashew nut shell oil diol) is the mass of polymerized cashew nut shell oil diol; and W (capping agent) is the mass of the acrylate compound containing active hydroxyl groups.
[0066] The light transmittance of the light-curing polyurethane acrylate film is tested according to the national standard GB / T 2410-2008, and the 180° peel strength is tested according to the national standard GB / T2792-1998.
[0067] Example 1
[0068] 100g of cashew nut shell oil diol with a hydroxyl value of 56mgKOH / g was added to a reactor, and after dehydration at 100°C for 2h under <-0.1MPa, the temperature was lowered to 50°C, 19.65g of 4,4'-dicyclohexylmethane diisocyanate and 20g of trimethylolpropane triacrylate were added, and the temperature was raised to 70°C under a nitrogen atmosphere (pressure was standard one atmosphere) for reaction for 2h, and then the temperature was lowered to 50°C to obtain a prepolymer, and then 0.05g of dibutyltin dilaurate and 5.8g of hydroxyethyl acrylate were added to the reactor, and the temperature was raised to 70°C under a nitrogen atmosphere (pressure was standard one atmosphere) for reaction for 3h, and then the reaction was stopped, the temperature was lowered and the material was discharged to obtain an aging-resistant light-curable polyurethane acrylate blended composition.
[0069] According to calculation, based on the total weight of the composition, the content of the active diluent is 13.74wt%, based on the weight of the photocurable polyurethane acrylate resin, the content of the soft segment is 79.69wt%, the content of the hard segment is 15.68wt%, and the content of the end-capping agent is 4.63wt%. The number average molecular weight of the polyurethane acrylate is 5098, and the viscosity of the composition at room temperature is 11200cps.
[0070] Example 2
[0071] 100g of cashew nut shell oil diol with a hydroxyl value of 55mgKOH / g was added to a reactor, and after dehydration at 100°C for 2h under <-0.1MPa, the temperature was lowered to 50°C, 17.47g of 4,4'-dicyclohexylmethane diisocyanate and 20g of triethylene glycol diacrylate were added, and the temperature was raised to 70°C under a nitrogen atmosphere (pressure was standard one atmosphere) for reaction for 2h, and then the temperature was lowered to 50°C to obtain a prepolymer, 0.05g of dibutyltin dilaurate and 3.87g of hydroxyethyl acrylate were added to the reactor, and the temperature was raised to 70°C under a nitrogen atmosphere (pressure was standard one atmosphere) for reaction for 3h, the reaction was stopped, the temperature was lowered and the material was discharged to obtain an aging-resistant light-curable polyurethane acrylate blended composition.
[0072] According to calculation, based on the total weight of the composition, the content of the active diluent is 14.14wt%, based on the weight of the photocurable polyurethane acrylate resin, the content of the soft segment is 82.40wt%, the content of the hard segment is 14.40wt%, and the content of the end-capping agent is 3.20wt%. The number average molecular weight of the polyurethane acrylate is 7082, and the viscosity of the composition at room temperature is 13300cps.
[0073] Example 3
[0074] 57g of cashew nut shell oil diol with a hydroxyl value of 98mgKOH / g was added into a reactor, and after dehydration at 110°C for 2h under <-0.1MPa, the temperature was lowered to 50°C, 17.47g of 4,4'-dicyclohexylmethane diisocyanate and 20g of triethylene glycol diacrylate were added, and the temperature was raised to 70°C for reaction for 2h under a nitrogen atmosphere (pressure was standard one atmosphere), and the temperature was lowered to 50°C, 0.05g of dibutyltin dilaurate and 3.87g of hydroxyethyl acrylate were added into the reactor, and the temperature was raised to 70°C for reaction for 3h under a nitrogen atmosphere (pressure was standard one atmosphere), and the reaction was stopped, the temperature was lowered and the material was discharged to obtain an aging-resistant light-curable polyurethane acrylate blended composition.
[0075] According to calculation, based on the total weight of the composition, the content of the active diluent is 20.32wt%, based on the weight of the photocurable polyurethane acrylate resin, the content of the soft segment is 71.79wt%, the content of the hard segment is 22.28wt%, and the content of the end-capping agent is 4.93wt%. The number average molecular weight of the polyurethane acrylate is 4710, and the viscosity of the composition at room temperature is 9430cps.
[0076] Example 4
[0077] 57g of cashew nut shell oil diol with a hydroxyl value of 98mgKOH / g was added into a reactor, and after dehydration at 110°C for 2h under <-0.1MPa, the temperature was lowered to 50°C, 16.38g of 4,4'-dicyclohexylmethane diisocyanate and 20g of triethylene glycol diacrylate were added, and the temperature was raised to 70°C for reaction for 2h under a nitrogen atmosphere (pressure was standard one atmosphere), and the temperature was lowered to 50°C, 0.05g of dibutyltin dilaurate and 2.90g of hydroxyethyl acrylate were added into the reactor, and the temperature was raised to 70°C for reaction for 3h under a nitrogen atmosphere (pressure was standard one atmosphere), and the reaction was stopped, and the temperature was lowered to discharge the material to obtain an aging-resistant light-curable polyurethane acrylate blended composition.
[0078] According to calculation, based on the total weight of the composition, the content of the active diluent is 20.76wt%, based on the weight of the photocurable polyurethane acrylate resin, the content of the soft segment is 74.67wt%, the content of the hard segment is 21.46wt%, and the content of the end-capping agent is 3.80wt%. The number average molecular weight of the polyurethane acrylate is 6120, and the viscosity of the composition at room temperature is 10600cps.
[0079] Comparative Example 1
[0080] 100g of polypropylene glycol with a hydroxyl value of 56mgKOH / g was added into a reactor, and after dehydration at 100°C for 2h under <-0.1MPa, the temperature was lowered to 50°C, 17.47g of 4,4'-dicyclohexylmethane diisocyanate and 20g of triethylene glycol diacrylate were added, and the temperature was raised to 70°C for reaction for 2h under a nitrogen atmosphere (pressure was standard one atmosphere), and the temperature was lowered to 50°C, 0.05g of dibutyltin dilaurate and 3.87g of hydroxyethyl acrylate were added into the reactor, and the temperature was raised to 70°C for reaction for 3h under a nitrogen atmosphere (pressure was standard one atmosphere), and the reaction was stopped, the temperature was lowered and the material was discharged to obtain an aging-resistant photocurable polyurethane acrylate blended composition.
[0081] According to calculation, based on the total weight of the composition, the content of the active diluent is 14.14wt%, based on the weight of the photocurable polyurethane acrylate resin, the content of the soft segment is 82.40wt%, the content of the hard segment is 14.40wt%, and the content of the end-capping agent is 3.20wt%. The number average molecular weight of the polyurethane acrylate is 7120, and the viscosity of the composition at room temperature is 11300cps.
[0082] Comparative Example 2
[0083] 50g of polypropylene glycol with a hydroxyl value of 112mgKOH / g was added into a reactor, and after dehydration at 110°C for 2h under <-0.1MPa, the temperature was lowered to 50°C, 17.47g of 4,4'-dicyclohexylmethane diisocyanate and 20g of triethylene glycol diacrylate were added, and the temperature was raised to 70°C for reaction for 2h under a nitrogen atmosphere (pressure was standard one atmosphere), and the temperature was lowered to 50°C, 0.05g of dibutyltin dilaurate and 3.87g of hydroxyethyl acrylate were added into the reactor, and the temperature was raised to 70°C for reaction for 3h under a nitrogen atmosphere (pressure was standard one atmosphere), and the reaction was stopped, the temperature was lowered and the material was discharged to obtain an aging-resistant photocurable polyurethane acrylate blended composition.
[0084] According to calculation, based on the total weight of the composition, the content of the active diluent is 21.88wt%, based on the weight of the photocurable polyurethane acrylate resin, the content of the soft segment is 70.04wt%, the content of the hard segment is 24.47wt%, and the content of the end-capping agent is 5.42wt%. The number average molecular weight of the polyurethane acrylate is 5110, and the viscosity of the composition at room temperature is 10800cps.
[0085] Comparative Example 3
[0086] 50g of polypropylene glycol with a hydroxyl value of 112mgKOH / g was added into a reactor, and after dehydration at 110°C for 2h under <-0.1MPa, the temperature was lowered to 50°C, 16.38g of 4,4'-dicyclohexylmethane diisocyanate and 20g of triethylene glycol diacrylate were added, and the temperature was raised to 70°C for reaction for 2h under a nitrogen atmosphere (pressure was standard one atmosphere), and the temperature was lowered to 50°C, 0.05g of dibutyltin dilaurate and 2.90g of hydroxyethyl acrylate were added into the reactor, and the temperature was raised to 70°C for reaction for 3h under a nitrogen atmosphere (pressure was standard one atmosphere), and the reaction was stopped, and the temperature was lowered to discharge the material to obtain an aging-resistant photocurable polyurethane acrylate blended composition.
[0087] According to calculation, based on the total weight of the composition, the content of the active diluent is 22.39wt%, based on the weight of the photocurable polyurethane acrylate resin, the content of the soft segment is 72.12wt%, the content of the hard segment is 23.63wt%, and the content of the end-capping agent is 4.18wt%. The number average molecular weight of the polyurethane acrylate is 6330, and the viscosity of the composition at room temperature is 11900cps.
[0088] Test Case
[0089] Take 100g of the polyurethane acrylate resin prepared in Examples 1-4 and Comparative Examples 1-3, add 3g of 184 initiator, stir evenly, dissolve, and then apply on PET release paper to form a film, so as to obtain an aging-resistant light-cured polyurethane acrylate film with a thickness of 0.2mm. Irradiate with a high-pressure mercury lamp with a wavelength of 365nm for 5min to ensure that the sample is completely cured, and test the transmittance by a UV-visible spectrophotometer. Test the 180° peel strength according to the national standard GB 2792-1998, and take the average value of 5 groups of experiments. The test results are shown in Table 1.
[0090] Table 1 Transmittance and peel force data
[0091]
[0092] It can be concluded from Table 1 that Examples 1-4, which introduce cashew nut shell oil diol as the soft segment, diisocyanate as the hard segment, and acrylate compounds as the polyurethane acrylate resin end-capping agent, can effectively improve the aging resistance of the film. After aging for 500 hours, the 180° peel strength is between 6.44-7.98N / 25mm, and the average visible light transmittance is >90%, which can meet the application in the field of optical display. The films prepared in Comparative Examples 1-3 have the problem of too low peel strength after aging.
[0093] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. An aging-resistant photocurable polyurethane acrylate blend composition, characterized in that: The anti-aging light-curable polyurethane acrylate blend composition comprises: Reactive diluent, double-bond terminated polyurethane acrylate resin; The double-bond terminated polyurethane acrylate resin comprises a soft segment, a hard segment and a capping agent; The soft segment is selected from cashew nut shell oil diol; The hard segment is selected from diisocyanates; The end-capping agent is selected from acrylic acid ester compounds containing active hydroxyl groups.
2. The aging-resistant photocurable polyurethane acrylate blend composition according to claim 1, characterized in that: The hydroxyl value of the cashew nut shell oil diol is 55 to 100 mgKOH / g; Preferably, the number average molecular weight of the double bond terminated polyurethane acrylate resin is 3000 to 10000; Preferably, the double-bond terminated polyurethane acrylate resin has a viscosity of 5000 to 15000 cps at 25°C.
3. The aging-resistant photocurable polyurethane acrylate blend composition according to claim 1, characterized in that: In the double-bond terminated polyurethane acrylate resin, the content of the soft segment is 60-90wt%, the content of the hard segment is 10-30wt%, and the content of the end-capping agent is 1-6wt%; Preferably, the diisocyanate is selected from at least one of isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and 1,4-cyclohexanedimethyl diisocyanate; Preferably, the acrylic acid ester compound containing active hydroxyl groups is selected from at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate and hydroxypropyl methacrylate.
4. The aging-resistant photocurable polyurethane acrylate blend composition according to claim 1, characterized in that: The active diluent is selected from at least one of cyclotrimethylolpropane formal acrylate, trimethylolpropane triacrylate, ethoxyethoxyethyl acrylate, acryloyl morpholine, pentaerythritol triacrylate, N-vinyl pyrrolidone, tripropylene glycol diacrylate, N-vinyl caprolactam, and triethylene glycol diacrylate; Preferably, in the anti-aging light-curable polyurethane acrylate blend composition, the content of the reactive diluent is 10 to 25 wt %; Preferably, the aging-resistant photocurable polyurethane acrylate blend composition also includes a catalyst, and the catalyst is selected from at least one of dibutyltin dilaurate, copper naphthenate, copper isooctanoate, iron naphthenate, iron isooctanoate, zinc naphthenate, zinc isooctanoate, lead naphthenate, lead isooctanoate, dibutyltin isooctyl thioglycolate, and dioctyltin diacetate.
5. The method for preparing the aging-resistant photocurable polyurethane acrylate blend composition according to any one of claims 1 to 4, characterized in that: The steps include: S1, placing a mixture containing cashew nut shell oil diol, diisocyanate, and active diluent in a reactor, and performing a prepolymerization reaction under an inactive atmosphere to obtain a prepolymer; S2. placing a mixture containing the prepolymer, the end-capping agent and the catalyst in a reactor, and performing an end-capping reaction under an inert atmosphere to generate a double-bond end-capped polyurethane acrylate resin, thereby obtaining the anti-aging photocurable polyurethane acrylate blend composition.
6. The preparation method according to claim 5, characterized in that: In step S1, the conditions of the prepolymerization reaction include: reaction temperature of 60-80° C., and reaction time of 1-4 h.
7. The preparation method according to claim 5, characterized in that: In step S1, the cashew nut shell oil diol is cashew nut shell oil diol that has been treated with dehydration; The dehydration treatment step comprises: placing the cashew nut shell oil diol that has not been dehydrated in a reactor, and dehydrating it at 90-120° C. for 1-4 hours under a vacuum environment.
8. The preparation method according to claim 5, characterized in that: In step S2, the conditions of the end-capping reaction include: reaction temperature of 60-80° C., and reaction time of 2-5 h.
9. The preparation method according to claim 5, characterized in that: In step S2, the catalyst is selected from at least one of dibutyltin dilaurate, copper naphthenate, copper isooctanoate, iron naphthenate, iron isooctanoate, zinc naphthenate, zinc isooctanoate, lead naphthenate, lead isooctanoate, dibutyltin isooctyl thioglycolate, and dioctyltin diacetate; Preferably, the catalyst is used in an amount of 0.01 to 0.5% of the weight of the prepolymer; Preferably, the amount of the end-capping agent is 2-5% of the weight of the prepolymer.
10. An OCA film, characterized in that: The OCA film is obtained by UV curing the aging-resistant photocurable polyurethane acrylate blend composition according to any one of claims 1 to 4.
Citation Information
Patent Citations
Ultraviolet-moisture dual-cured modified organosilicon adhesive and preparation method therefor
CN105505302A
Adhesive tape
JP2005136298A